Pengaruh Kompetensi Guru Dalam Penggunaan Teknologi Pembelajaran Untuk Meningkatkan Motivasi Belajar Siswa - Umisara, Elinda (LPPPI Publishing, 2024)
This study aims to examine the influence of the relationship between teacher competence in using learning technology and student learning motivation. The study utilized a sample of 30 respondents, collecting data through a questionnaire to measure scores of teacher competence (X) and student learning motivation (Y). Correlation analysis yielded a correlation coefficient (r_xy) of 0.880, indicating a significant positive relationship between the two variables. The findings emphasize the importance of investing in training and developing teachers' abilities to effectively utilize technology as a supportive tool in the learning process. The practical implications of this research underscore the need for ongoing support from schools and governments to facilitate better and adequate integration of technology into the educational curriculum, with the aim of enhancing overall student learning motivation and supporting improved learning outcomes.